A Holistic Model for Character Education in Schools (An Alternative Educational Model) - Abdul Khobir; Sopiah; Fatmawati Nur Hasanah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This research discusses “A Holistic Model for Character Education in Schools.” Character education is considered an important solution to a variety of ongoing moral vulnerability phenomena. It is expected that through education the cognitive, affective, psychomotor, and spiritual aspects in learners can be harmonized. To this end, a holistic model for character education can be applied to learners. This study was carried out using a qualitative approach through library research. The data were collected by documentation technique and later analyzed by descriptive analysis. The research results indicated that character education is a process of positive values internalization in learners for them to possess good character, which comprises cognitive, feeling, and action aspects. Therefore, it is deemed necessary to introduce and internalize life values that are useful for learners to become whole human beings, that is, as individual-social, physical-spiritual, or autonomous-God’s human beings. The holistic character education model can be implemented in schools in an integrated manner across all school subjects. Otherwise put, it can be implemented through the learning process at school on a day-to-day basis.